ATOPIC DERMATITIS: IMPROVING EARLY DETECTION AND PREVENTION MEASURES IN THE COMMUNITY SETTING - Wisnu Barlianto; Desy Wulandari; Charity Monica; Nisak Humairok (Caring : Jurnal Pengabdian Masyarakat, 2021)
Atopic dermatitis is a chronic inflammation of the skin characterized by disruption of the skin barrier and aberrations in the immune response. In general, atopic dermatitis can be affected by various complex interactions including genetics, diet, and stress. The lack of public attention to atopic dermatitis which often affects children is one of the factors for the increasing prevalence of atopic dermatitis. The purpose of this community service is to help the community understand the importance of early detection and allergy prevention efforts. Community service is carried out by holding online seminars that can be followed by the general public as well as direct consultations and discussions with pediatricians for allergy patients at the Department of Pediatrics at Dr. RSUD Dr. Saiful Anwar Malang. The total Immunoglobulin E level of the respondents was measured using the enzyme-linked immunosorbent assay method. The severity of the respondents was determined by calculating the SCORAD index. The results of early detection showed that 100% of respondents had intrinsic atopic dermatitis, 90% with mild severity and 10% with moderate severity. After being checked for allergies, the respondents received the appropriate supplements. Conclusion: By holding this community service activity, ordinary people become more aware of the importance of treating allergic diseases as early as possible because the incidence of atopic dermatitis can be reduced and the quality of life of patients can be improved. This outreach activity must be carried out continuously in the following years.